Proceedings of the 10th International Conference on Computer Recognition Systems CORES 2017 (Advances in Intelligent Systems and Computing,, 2018)
This book offers a comprehensive study of computer recognition systems - one of the most promising directions in artificial intelligence. It presents a collection of 52 carefully selected articles contributed by experts in the field of pattern recognition, discussing both methodological aspects and applications of current research. It includes the following sections: · Features, learning, and classifiers · Biometrics · Data stream classification and big data analytics · Image processing and computer vision · Medical applications · Applications It is a valuable reference tool for scientists dealing with the problems of designing computer pattern recognition systems, including researchers and students of computer science, artificial intelligence and robotics.